The Concept of Knowledge Transmission in Ibn Taimiyah’s Thought: A Study of Revelation, Reason, and the Senses as Knowledge Channels in Islam - Samsuddin, Samsuddin; Iskandar, Iskandar; Agusman, Agusman; Shamsul, Mariyanto Nur (Islamic Studies in the World, 2024)
Background. Islam places knowledge in a noble position, and the tradition of knowledge in Islam has produced many great scholars throughout history. However, this intellectual tradition has not only generated knowledge but also sparked various debates and discussions about the concept of knowledge itself. One scholar who gave significant attention to the concept of knowledge was Ibn Taimiyah, particularly regarding the channels of knowledge. His thoughts on how knowledge is transmitted have become an essential part of scholarly discussions within the Islamic intellectual tradition. Purpose. The purposes of this research were to analyze and describe the concept of knowledge transmission according to Ibn Taimiyah. Method. This research is a type of library research using descriptive qualitative methods with a historical and philosophical approach. Results. The results of this research show that there are three transmissions and channels of knowledge in Ibn Taimiyah’s perspective: revelation (wahyu), reason, and the senses. There is no conflict between the three. However, revelation is the absolute and main channel of knowledge. while reason and senses are channels of knowledge that must be subject to revelation. Both play a role in digesting and understanding the truth that comes from revelation. Conclusion. Based on the discussion, it can be concluded that the channels of knowledge according to Ibn Taimiyah are (wahyu) revelation, aql (mind) and the senses. There is no conflict at all between the three channels. But wahyu (revelation) is the most important and absolute channel.